If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying t(6t + -7) = 0 Reorder the terms: t(-7 + 6t) = 0 (-7 * t + 6t * t) = 0 (-7t + 6t2) = 0 Solving -7t + 6t2 = 0 Solving for variable 't'. Factor out the Greatest Common Factor (GCF), 't'. t(-7 + 6t) = 0Subproblem 1
Set the factor 't' equal to zero and attempt to solve: Simplifying t = 0 Solving t = 0 Move all terms containing t to the left, all other terms to the right. Simplifying t = 0Subproblem 2
Set the factor '(-7 + 6t)' equal to zero and attempt to solve: Simplifying -7 + 6t = 0 Solving -7 + 6t = 0 Move all terms containing t to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 6t = 0 + 7 Combine like terms: -7 + 7 = 0 0 + 6t = 0 + 7 6t = 0 + 7 Combine like terms: 0 + 7 = 7 6t = 7 Divide each side by '6'. t = 1.166666667 Simplifying t = 1.166666667Solution
t = {0, 1.166666667}
| -4(x+2)-3(5+x)=0 | | 9x^2=40x-16 | | 2(60+3w)+2w=520 | | 33x+54x=500 | | 15+2b=-9 | | 3(w+8)+8w=13 | | 15y+40x=350 | | 4x^2+4x-1=9 | | 4x+2x=5x+3 | | n+1+n+2+n+3=99 | | 28=2(u-4)+2u | | 9x^2-21x-2=13 | | 6x+152+2x+12=180 | | 0.8x=-1.2 | | 8b-4b-6b-8=2b | | 0.8x=-3.6 | | 4x+0.8=24 | | 4x-8=-26 | | 0.5m-3.6=-5.8+2.7 | | 2(4+2k)=k-10 | | 6x+12+2x+72=180 | | 20-2x+22=52 | | 3.75=ln(q+4) | | T=-16t^2+45t+50 | | 6.6=(11-10x)0.3 | | 6x+12+2x+72=90 | | 1.075x=30 | | -49=69-13-4g | | (4x+4)(3x-5)=0 | | 4b-6-5b+8= | | -5x-1=3-6x | | 6x-38+3x-16=90 |